2018
DOI: 10.2196/ijmr.9001
|View full text |Cite
|
Sign up to set email alerts
|

Usage, Acceptability, and Effectiveness of an Activity Tracker in a Randomized Trial of a Workplace Sitting Intervention: Mixed-Methods Evaluation

Abstract: BackgroundWearable activity trackers are now a common feature of workplace wellness programs; however, their ability to impact sitting time (the behavior in which most of the desk-based workday is spent) is relatively unknown. This study evaluated the LUMOback, an activity tracker that targets sitting time, as part of a cluster-randomized workplace sitting intervention in desk-based office workers.ObjectiveStudy objectives were to explore: (1) office workers’ self-directed LUMOback use, (2) individual-level ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
0
16
1
Order By: Relevance
“…The LUMOback also provides real-time prompts when the user is in a poor (slumped) lumbar posture and when the user engages in prolonged periods of sitting time (user-defined, prompts can be set from 15 min to 2 h). Usage of the LUMOback in the Stand Up Lendlease trial was low (median of eight days use in the first three months) and has been reported in more detail in a previous publication [ 20 ].…”
Section: Methodsmentioning
confidence: 94%
“…The LUMOback also provides real-time prompts when the user is in a poor (slumped) lumbar posture and when the user engages in prolonged periods of sitting time (user-defined, prompts can be set from 15 min to 2 h). Usage of the LUMOback in the Stand Up Lendlease trial was low (median of eight days use in the first three months) and has been reported in more detail in a previous publication [ 20 ].…”
Section: Methodsmentioning
confidence: 94%
“…Wearable devices have significant potential for health monitoring and they are being widely investigated [ 8 - 13 ]. As a very popular tool, the use of wearable devices in medical and fitness applications is rapidly increasing.…”
Section: Introductionmentioning
confidence: 99%
“…The findings in our cohort suggest that reactivity is not problematic in older people. However, this might be device-specific as the attachment method and size of the activPAL is relatively unobtrusive compared to other devices [21].…”
Section: Discussionmentioning
confidence: 99%